I am having a hard time with an Algebra question on systems of equations and graphing: y= 5x-8
y= -5x+2

The answer choices are:
A. The solution is ______( fill in whatever the solution is)__.
B. There is infinitely many solutions.
C. There is no solution.
I also have to graph it so what what would I graph if need be?
Thanks so much!!!

Answers

Answer 1
Answer: 1)First you substitute what we already know y equals
-5x+2=5x-8
2) if you solve that you get that x=1
3) put x back in one of the original equations
y=5(1)-8
4) then you get y as -2

A) the solution is x=1 y=-2

You would graph x and y and a coordinate point (1,-2)

Related Questions

Let n = 5. What is the value of 4n − 3?A. 8B. 17 C. 20 D. 23
Using the factorised trinomial , prove that there are only two values of n for which is a prime number.
Solve the equation 3-x/5-4-x/2=1
Rachel plays a game by rolling two number cubes with side's numbered 1 through 6. To win the game, the sum of the numbers facing up must be 11. What is the probability that Rachel will win the game
Ex 3.712. find the area between the curve y=x³-2 and the y-axis between y= -1 and y=25

∠E and ∠F are vertical angles with m∠E=8x+8 and m∠F=2x+38.

What is the value of x?

Answers

As they are vertical angles, their magnitude will be equal.
8x+8 = 2x+38
8x-2x = 38-8
6x = 30
x = 5

So, Your Final Answer would be 5

Hope this helps!

Your Final Answer would be 5

Hope this helps!

5x-8 (4x-7)=2 solve for x

Answers

5x - 8(4x - 7) = 2

First, expand your problem. / Your problem should look like: 5x - 32x + 56 = 2
Second, simplify 5x - 32x + 56. / Your problem should look like: -27x + 56 = 2
Third, subtract 56 from both sides. / Your problem should look like: -27x = 2 - 56
Fourth, subtract 2 - 56 to get -54. / Your problem should look like: -27x = -54
Fifth, divide both sides by -27. / Your problem should look like: x =  (-54)/(-27)
Sixth, simplify the fraction to - (54)/(27) / Your problem should look like: x =  (54)/(27)
Seventh, simplify. / Your problem should look like: x = 2

Answer: x = 2

True or False: Only like terms can be combined. A True B False

Answers

Answer:

True

Step-by-step explanation:

Like terms like 4x-3x the x term. is a like term

6-4x can be subtracted because they aren't the same.

High Hopes^^

Barry-

Answer:

i believe this false but im not positive

What is the inverse of y=4x-2

Answers

y=4x-2\n \nreverse \ the \ x \ and \ y \ to \ get \n \n x=4y-2 \n \n solve \ for \ the \ new \ y \ to \ get \n \n4y =x+2 \ \ / :4 \n \ny=(x)/(4) + (2)/(4) \n \ny=(1)/(4)x + (1)/(2)\n \n The \ answer \ is : \n \n y=(1)/(4)x + (1)/(2)
 y=4x-2

change:

x = 4y - 2
4y = x + 2
y = x/4 + 1/2   <--- inverse

Mass of propane = 4,300 g

Volume of propane = 10,000 mL

Answers

What's the Question? or the Problem you need Help

5. What is a cubic polynomial function in standard form with zeros 1, –2, and 2? (1 point)= x3 + x2 – 3x + 4
= x3 + x2 – 4x – 2
= x3 + x2 + 4x + 4
= x3 – x2 – 4x + 4

Answers

Answer:

Option D is correct

The cubic polynomial function in standard form is :

x^3-x^2-4x+4

Step-by-step explanation:

Given the zeroes of the polynomial function 1 , -2 and 2.

i.e,   x = 1 , -2 and 2  where x is the zero of the polynomial function.

we can write this as

x - 1 = 0,

x + 2 = 0 or

x - 2 = 0  

(x - 1)(x + 2)(x - 2) =0  

Using identities (a+b)(a-b) =a^2-b^2

then;

(x-1)(x^2-4)=0

Multiply the first term of the first expression with second expression;

x (x^2-4) =x^3-4x

also,

Multiply the second term of the first expression with second expression;

1(x^2-4) = x^2 -4

Now, subtract x^3-4x and x^2 -4

we get;

x^3-4x-x^2+4

then, we have;

x^3-x^2-4x+4=0

Cubic function is any function of the form y = ax^3 + bx^2 + cx + d, where a, b, c, and d are constants and a≠0

therefore, the given function is cubic function;

so, the cubic function f(x) = x^3-x^2-4x+4


Hello,

Answer D
(x-1)(x+2)(x-2)=(x-1)(x²-4)=x^3-x²-4x+4